Tingkat Kepuasan Petani Sawit Terhadap Pelayanan Lembaga Pemasaran Di Kecamatan Penarik Kabupaten Mukomuko - Era Impiani; Reswita Reswita; Ketut Sukiyono (Agric, 2020)
This research aims to identify service attributes based on the level of importance and performance according to palm oil farmers, knowing the level of satisfaction of oil palm farmers on the services that have been carried out by market institutions, knowing the level of satisfaction of oil Palm Farmers to the services carried out by Palm Oil Mill in Penarik District, Mukomuko Regency. This research was conducted in August 2018 on 80 respondents, namely 75 farmers and 5 marketing institutions. Research location determinedby using the two stage cluster sampling method. The data analysis methods used are Descriptive Analysis, Importance Performance Analysis (IPA), and the Customer Satisfaction Index (CSI). The result is that the service attributes that need to be improved by marketing institutions are the appropriate prices, time to pay, accuracy of weighing and honesty in service. Then the attributes that need to be improved in Palm Oil Mill are prices that match the accuracy of weighing and honesty in service. CSI values ​​on farmer respondents to marketing institutions were 74.67% and CSI values ​​on farmer respondents to Palm Oil Mill were 79.09%. Overall the level of satisfaction of oil palm farmers towards toke marketing services and PKS services is in the Satisfied category. The level of satisfaction to the MCC service is satisfied with the CSI index of 68.05%. Keywords: Oil Palm Farmers, Marketing, IPA, CSI, Satisfaction.